2016
DOI: 10.1158/1541-7786.mcr-16-0097
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylome Analyses Implicate Fallopian Tube Epithelia as the Origin for High-Grade Serous Ovarian Cancer

Abstract: High-grade serous ovarian cancer (HGSC) is the most common and lethal form of epithelial ovarian cancer (EOC). Two distinct tissues have been suggested as the tissue of origin: ovarian surface epithelia (OSE) and fallopian tube epithelia (FTE). We hypothesized that the DNA methylome of HGSC should more closely resemble the methylome of its tissue of origin. To this end, we profiled HGSC (n=10), and patient-matched OSE and FTE (n=5) primary fresh-frozen tissues, and analyzed the DNA methylome using Illumina 450… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 48 publications
4
45
0
Order By: Relevance
“…In addition to genomic characteristics, these EOC histotypes have different epidemiologic risk factors [24], expression signatures [57], clinical responses to therapy [8] and distinct precursor sites. HGSOC appears to originate from fallopian tube or ovarian surface epithelium [9], shows few mutational events compared with other histotypes [10] and generally have gross chromosomal instability exhibiting copy number variations [11,12]. LGSOC are considered to arise from borderline tumors [13] and commonly possess mutations in the Ras family of genes ( KRAS, BRAF, NRAS, ERBB2 , and PTEN ) and are chromosomally stable [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to genomic characteristics, these EOC histotypes have different epidemiologic risk factors [24], expression signatures [57], clinical responses to therapy [8] and distinct precursor sites. HGSOC appears to originate from fallopian tube or ovarian surface epithelium [9], shows few mutational events compared with other histotypes [10] and generally have gross chromosomal instability exhibiting copy number variations [11,12]. LGSOC are considered to arise from borderline tumors [13] and commonly possess mutations in the Ras family of genes ( KRAS, BRAF, NRAS, ERBB2 , and PTEN ) and are chromosomally stable [14].…”
Section: Introductionmentioning
confidence: 99%
“…As evidence of an FTE origin, several studies identified putative precursor lesions in the fallopian tube of women undergoing prophylactic oophorectomy called p53 signatures, which were patches of secretory epithelium that express mutant p53 protein [24]. The transcriptomic profile of HGSOC tumors significantly correlated with that of the fallopian tube [5], and the genomic methylation patterns of HGSOC were more similar to the FTE than the OSE [6]. A recent retrospective analysis found salpingectomy was associated with a 45% decrease in ovarian cancer risk [7].…”
Section: Introductionmentioning
confidence: 99%
“…We downloaded and reprocessed external DNA methylation data on normal cell types from prior publications (Patch et al 2015;Klinkebiel et al 2016) (methods), including normal FTE and ovary stroma, profiled on the earlier generation of the Infinium platform, Infinium HumanMethylation450 (450K) array. The intersect between the two platforms (450,161 CpGs) were used in joint analysis with these external normal controls.…”
Section: Resultsmentioning
confidence: 99%
“…Public available data resources DNA methylation data (Illumina HM450 array) of ovarian stroma samples (N=4; samples annotated as ovary and pathologist evaluation of available slides confirms ovarian stroma histology) were downloaded from the Genomic Data Commons (GDC) Data Portal (https://portal.gdc.cancer.gov), together with that of Uterine Carcinosarcoma (UCS; N=57) and Sarcoma (SARC; N=261). Pure, uncultured fallopian tube epithelium samples (FTE; N=4) were downloaded through GEO database, with one sample GSM2146822 taken from Series GSE81224 (Klinkebiel et al 2016), and the other three samples (GSM1606969, GSM1606970, and GSM1606973) from Series GSE65820 (Patch et al 2015). Other FTE samples in the same studies either had insufficient epithelial purity or had undergone in vitro culturing and therefore not included.…”
Section: Unsupervised and Supervised Dna Methylation Analysismentioning
confidence: 99%